Co-constructing globalizing music education through an intercultural professional learning community - A critical participatory action research in Nepal - Timonen, Vilma (My University, 2020)
This doctoral dissertation addresses the increasing diversity in globalising 21st-century societies through an intercultural, inter-institutional critical participatory action research (PAR) project that engaged music educators and teacher educators from Finland and Nepal in collaborative learning. The inquiry is based on a social and educational vision according to which collaborative learning across national and institutional borders is seen as a powerful way for music teacher education to respond to the growing challenges of diversity. The PAR design highlights a more democratic, inclusive, and balanced approach to research and, as such, aims to challenge the Western hegemony in academic knowledge production. The inquiry is furthermore based on the conviction that the need for decolonising music teacher education is both real and imminent and can be effectively addressed through creating collaborative learning opportunities for educators from diverse backgrounds. Following the works of Arjun Appadurai, we should consider the right to research a universal right, and by inclusively expanding its reach we can provide opportunities to navigate through different knowledge paths and realize the potential to rejuvenate music teacher education practices and research both locally and globally. The inquiry was guided by the following research questions: 1) What kinds of potentials and constraints does critical collaborative intercultural educational development work hold for a) music educators’ professional development, b) music teacher education practices and, c) music education scholarship? 2) What kinds of politics were involved in the critical intercultural educational development work between the Finnish and Nepali music educators and researchers? These research questions were answered in three peer-reviewed, single and co-authored articles published in international publications, each guided by their own sub-questions; the complete texts can be found in the appendices of this summary. The empirical material of this inquiry was generated from 2013- 2019 during the process of manifold collaborative activities among Finnish and Nepali music educators working towards educational devel- opment at individual, institutional, and global levels. The analysis utilises theoretical lenses from the disciplines of music and music teacher education research, intercultural (music) education research, professional learning, and organizational studies. Article I illustrates how intercultural collaborative educational work is inevitably shaped by the affective actions and organisational micropolitics that are inherent to the process of the participating educators’ professional re-invention. The article points out the necessity of incorporating the emotional dimensions of educators’ lives as central elements in any educational development work. Article II scrutinizes the Finnish-Nepali collaboration through the theoretical lenses of a professional learning community (PLC), and, explores how the features of PLC acted as catalysts or constraints in the process of intercultural educational development work. Further to that point, article II illustrates the nature of learning that took place in the intercultural PLC and argues that collaborative learning should be embedded in the institutional structures of music teacher education. Article III explores the ambivalent duality in the risk of manifesting colonial power during such work, and the potential for the transformation of professional identity omnipresent in intercultural dialogues. The findings of article III highlight the potential for epistemic reflexivity in such intercultural interactions, but similarly illustrate how the colonial setting inevitably frames the dialogue and leaves the politics of reflexivity open, with no final answers being proffered. The discussion then expands upon the potentials and constraints of the critical collaborative intercultural educational development work for music educators’ professional learning, professional education, and research. Leaning on the work of Gert Biesta, it argues that ensuring music teaching that is educational requires supporting music educators to take a stance as critical knowledge workers that are supported in developing ethically engaged music teaching practices through research. The discussion emphasises that the efforts of co-constructing globalizing music education call for developing trust on multiple levels. Music educators need support to develop trust in their own abilities in uncertain situations, and they need to be seen as trusted active agents of change within their institutions. The institutional development in music teacher education calls for developing systematic collaborative practices that support the ability of music teacher institutions to act as innovative knowledge communities, both locally and globally. Moreover, it is argued that music education research would benefit from developing trust in multivoiced knowledge production, which would be supported by critical, participatory, and interdisciplinary research approaches. Finally, the discussion offers a vision for a 21st-century globalizing music education, in which music education is elevated by providing music educators opportunities for ongoing critical collaborative professional learning in institutions that can be characterized as innovative knowledge communities. This vision highlights the belief that engaging practitioners in critical, multivoiced, and collaborative research can provide a compelling environment for rejuvenating research ideas, and also contribute meaningfully to co-constructing the future of music education. The research has been conducted as part of a larger research project, “Global visions through mobilizing networks: Co-developing intercultural music teacher education in Finland, Israel, and Nepal”.

Tässä artikkelimuotoisessa väitöskirjassa raportoidaan kulttuurien ja instituutioiden välinen kriittinen, osallistava toimintatutkimus (PAR), joka käsittelee globalisoituvien 2000-luvun yhteiskuntien lisääntyvää monimuotoisuutta. Tutkimuksessa tarkastellaan musiikin opetuksen ja tutkimuksen käytäntöjä ja niiden kehittämisen mahdollisuuksia ja haasteita suomalaisten ja nepalilaisten musiikinopettajien ja opettajankouluttajien yhteistoiminnallisen ammatillisen kehittymisen ja oppimisen prosessin kautta. Tutkimus perustuu sosiaalis-kasvatukselliseen näkemykseen, jonka mukaan kansalliset ja institutionaaliset rajat ylittävä, kollaboratiivinen oppiminen nähdään tapana vastata monimuotoisuudesta aiheutuviin haasteisiin musiikinopettajien koulutuksessa, opettajien ammatillisen kehittymisen prosesseissa sekä musiikkikasvatuksen tutkimuksessa. PAR-malli korostaa demokraattisempaa, osallistavampaa ja tasapainoisempaa lähestymistapaa tutkimukseen ja pyrkii sellaisenaan haastamaan länsimaista hegemoniaa akateemisen tiedon tuottamisessa. Lisäksi tutkimuksen taustalla on käsitys musiikinopettajien koulutuksen dekolonisaation tarpeesta, johon voidaan vastata muun muassa luomalla yhteistyömahdollisuuksia erilaisista taustoista peräisin oleville kouluttajille. Työ kiinnittyy Arjun Appadurain teorioihin, joiden mukaan oikeus tutkimukseen ja tutkittuun tietoon on yleismaailmallinen perusoikeus. Inklusiivisuus akateemisessa tiedontuotossa ja tutkimuksellisen osaamisen kehittäminen mahdollistavat koulutus- ja tutkimuskäytäntöjen uudistamisen sekä paikallisesti että globaalisti. Tutkimusta ovat ohjanneet seuraavat tutkimuskysymykset: 1) Millaisia mahdollisuuksia ja haasteita kriittinen, kulttuurienvälinen koulutuksen kehittämistyö sisältää a) musiikinopettajien ammatilliselle kehitykselle, b) musiikinopettajien koulutuskäytännöille ja c) musiikkikasvatuksen tutkimukselle? ja 2) Millaista politiikkaa liittyy suomalaisten ja nepalilaisten musiikinopettajien ja tutkijoiden kriittiseen, kulttuurienväliseen koulutuksen kehittämistyöhön? Tutkimuskysymyksiin vastattiin kolmessa vertaisarvioidussa artikkelissa, jotka on julkaistu kansainvälisissä jul- kaisuissa. Kutakin artikkelia ohjasivat erityiset alakysymykset. Tutkimuksen empiirinen aineisto syntyi kriittisessä toimintatutkimuksessa vuosina 2013–2019, jonka puitteissa suomalaiset ja nepalilaiset musiikinopettajat työskentelivät kohti koulutuksen kehittämistä yksilöllisellä, institutionaalisella ja globaalilla tasolla. Analyysissä hyödynnetään teoreettisia linssejä musiikin ja musiikinopettajien koulutuksen, kulttuurienvälisen (musiikki)kasvatustutkimuksen, ammatillisen oppimisen ja organisaatiotutkimuksen aloilta. Artikkelissa I analysoidaan, kuinka kulttuurienvälistä ja yhteistyöhön perustuvaa koulutusyhteistyötä väistämättä värittävät erilaiset sosio-emotionaaliset ulottuvuudet, jotka asettavat tietyt reunaehdot osallistuvien opettajien ammatillisen kehittymisen prosesseille. Analyysissa nostetaan esiin tarve sisällyttää emotionaaliset ulottuvuudet keskeisiksi tekijöiksi missä tahansa koulutuksen kehittämistyössä. Artikkelissa II tarkastellaan Suomen ja Nepalin välistä yhteistyötä ammatillisen oppimisyhteisön (PLC) käsitteen näkökulmasta ja tutkitaan, miten PLC:n ominaisuudet toimivat katalysaattoreina tai haasteina kulttuurienvälisessä koulutuksen kehittämistyössä. Artikkeli II havainnollistaa suomalais-nepalilaisessa kulttuurienvälisessä PLC: ssä tapahtunutta oppimisen luonnetta. Artikkeli III tarkastelee episteemisen refleksiivisyyden mahdollisuutta kulttuurienvälisessä ammatillisessa vuorovaikutuksessa ja analysoi, kuinka kolonialismi väistämättä värittää interkulttuurista dialogia. Tämä kaksitahoisuus on leimallista kulttuurien väliselle koulutuksen kehittämistyölle, jossa refleksiivisen politiikan kysymykset jäävät avoimeksi. Tiivistelmän diskussio laajentaa ymmärrystä kriittisen, kollaboratiivisen ja kulttuurienvälisen koulutuksen kehittämistyön mahdollisuuksista sekä haasteista musiikinopettajien ammatilliselle oppimiselle, ammatilliselle koulutukselle ja tutkimukselle. Gert Biestaa mukaillen väitöskirja argumentoi, että kasvatuksellisesti mielekkään musiikinopetuksen varmistaminen edellyttää, että musiikinopettajat nähdään kriittisinä tietotyöntekijöinä, joita tutkimuksellisuuteen kannustamisen avulla tuetaan eettisesti sitoutuneiden musiikin opetuskäytäntöjen kehittämisessä.Työn päätelminä esitetään, että globalisoituvan musiikkikasvatuksen jaettu kehittämistyö edellyttää luottamuksen kehittämistä yksilöllisellä, institutionaalisella sekä globaalilla ta- solla. Yhtäältä musiikinopettajat tarvitsevat tukea kehittääkseen luottamusta omiin kykyihinsä muuttuvissa toimintaympäristöissä, ja heidät olisi nähtävä luotettuina, aktiivisina muutoksen tekijöinä omissa organisaatioissaan. Toisaalta musiikinopettajakoulutuksen kehittäminen edellyttää järjestelmällisten yhteistyökäytäntöjen kehittämistä, jotka tukevat musiikin opettajakoulutuslaitosten kykyä toimia innovatiivisina tietoyhteisöinä sekä paikallisesti että maailmanlaajuisesti. Lisäksi työssä argumentoidaan, että musiikkikasvatuksen tutkimukselle olisi hyötyä luottamuksesta moniääniseen tiedon tuotantoon, jota tuetaan kriittisillä, osallistavilla ja tieteidenvälisillä tutkimusmenetelmillä. Lopuksi väitöskirja esittää vision globaalista 2000-luvun musiikkikasvatuksesta, jossa musiikkikoulutusta kehitetään tarjoamalla musiikinopettajille mahdollisuuksia jatkuvaan, kriittiseen ja yhteistyöhön perustuvaan ammatilliseen oppimiseen organisaatioissa, joita voidaan luonnehtia innovatiivisiksi tietoyhteisöiksi. Visio korostaa uskoa siihen, että toimijoiden osallistaminen kriittiseen, moniääniseen tutkimukseen tarjoaa houkuttelevan ympäristön rohkeille tutkimusideoille ja samalla myötävaikuttaa merkittävästi kasvatuksellisesti mielekkään musiikin koulutuksen ja tutkimuksen tulevaisuuden rakentumiseen. Tutkimus on toteutettu osana laajempaa tutkimushanketta “Globaaleja visioita verkostoitumalla”.
Keywords: musiikkikasvatus; MuTri